Durability Assessment of Cylinder Block for Two Stroke Free Piston Linear Engine using Random Loading - M. M., Rahman; M. M., Noor; R. A., Bakar; A. K., Ariffin (Science Publications, 2009)
This research presents the durability assessment of cylinder block for a two-stroke free piston engine using narrow band approach. The life prediction results are worthy for improving the component design at the very early developing stage. This approach is adequate for periodic loading, however, requires very large time records to accurately describe random loading processes. Fatigue damage in conventionally determined from time signals of the loading, frequently in the form of stress and strain. However, there are scenarios when a spectral form of loading is more appropriate. In this case the loading is defined in terms of its magnitude at different frequencies in the form of a Power Spectral Density (PSD) plot. The vibration fatigue calculation can be utilized where the random loading and response are categorized using power spectral density functions and the dynamic structure is modeled as a linear transfer function. This research also investigates the effect of the mean stress on the fatigue life prediction using the random loading. The acquired results indicate that the Goodman mean stress correction method gives the most conservative results with the Gerber and no (zero) mean stress method. It is observed that the compressive mean stresses are beneficial while the tensile mean stresses are detrimental to the fatigue life. The proposed technique is capable of determining premature products failure phenomena. Therefore, this technique is able to reduce cost, time to market, improve the product reliability and finally the user confidence.